Development and Evaluation of Interactive Video: An Instructional Material for Teaching Plumbing System - Chiu, Charmine; Tito, Renefer Isidore B.; Lumactod, Mariell; Dumadag, Christopher; Rosales, Victor S.; Sumaylo, Glay Vhincent C. (Journal of Social and Scientific Education, 2025)
In the era of an ICT-driven educational landscape, engaging students in technical-vocational subjects remains a challenge, particularly in the plumbing trade, where there is a shortage of skilled practitioners and qualified trainers. This study aimed to develop and evaluate the acceptability of an interactive instructional video on the plumbing system to address both engagement and skill development needs. A developmental research method, guided by the ADDIE Model, was employed in designing videos, emphasizing content design, media design, visual design, assessment items, feedback mechanisms, and navigation. These features are intended to capture students’ interest, promote active engagement, and enhance appreciation of plumbing as both an academic subject and a viable trade. Purposive sampling was used to select 30 respondents: three (3) plumbing instructors, two (2) educational technology teachers, and twenty-five (25) third-year students majoring in Industrial Arts. The data were gathered using a modified survey questionnaire with a 5-point Likert scale and analyzed through descriptive statistics (frequency distribution, mean, standard deviation) and a Welch’s Independent T-test to compare teacher and student evaluations. Results indicated that respondents rated the video as excellent overall, with navigation receiving the highest scores, followed by assessment. Group comparisons showed that students gave consistently higher ratings than teachers. Despite differences in experience, the consistently high ratings from both groups suggest that the developed interactive video holds strong potential as an instructional material for teaching the plumbing system, addressing classroom engagement challenges, and contributing to the development of skills in the plumbing industry.